Kebiasaan Gen Z dalam Membentuk Kebiasaan Konsumsi Coklat Dubai Ditinjau pada Peran Media Sosial - Natasya Sarah Mountina; Prima Mulyasari Agustini (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
The development of social media has changed the way Generation Z shapes their preferences and consumption decisions. This research aims to understand how social media exposure, particularly through content from influencers and peer communities, influences perceptions and purchasing decisions towards Dubai chocolate products. Using a descriptive qualitative approach and phenomenological methods, data was collected from interviews with ten informants and one triangulator. The results were analyzed using Social Judgment Theory and Social Construction of Reality. The findings show that exposure to digital content is able to shift an individual's initial attitude from indifference to acceptance, as well as forming a collective meaning towards the product as a symbol of lifestyle, social status and digital identity. Dubai chocolate consumption is not only functional, but also symbolic, reflecting a shift in consumption paradigm among Gen Z. This research recommends the importance of marketing strategies based on social narratives and critical awareness in facing digital trends.